Evidence of Bidirectional Associations Between Depressive Symptoms and Body Mass Among Older Adults. (7th March 2019) - Emery, Charles F; Finkel, Deborah; Gatz, Margaret; Dahl Aslan, Anna K
Abstract: Objectives: Body fat, measured with body mass index (BMI), and obesity are associated with depressive symptoms. Among younger adults there is stronger evidence of obesity leading to depressive symptoms than of depressive symptoms leading to obesity, but the temporal relationship is unknown among older adults. This study utilized dual-change-score models (DCSMs) to determine the directional relationship between body mass and depressive symptoms among older adults. Method: Participants ( n = 1, 743) from the Swedish Twin Registry (baseline age range 50–96 years) completed at least one assessment of BMI (nurse measurement of height and weight) and the Center for Epidemiologic Studies-Depression scale (CESD). More than half the sample completed 3 or more assessments, scheduled at intervals of 2–4 years. DCSMs modeled the relationship of BMI and CESD across age, both independently and as part of bivariate relationships. Results: Depressive symptoms contributed to subsequent changes in BMI after age 70, while BMI contributed to subsequent changes in depressive symptoms after age 82. Thus, there is a reciprocal relationship that may change with age. The effect was more pronounced for women. Discussion: The association of BMI and depressive symptoms is bidirectional among older adults, and it appears to be affected by both age and sex.